Synthesis and Antibacterial Screening of Some Pyrazine-carboxamidomethyl Derivatives - Jha, A.K.; Asthana, J.G.; Trivedi, N.K. (Asian Journal of Chemistry, 2010)
Some pyrazinecarboxamidomethyl derivatives were synthesized and screened for their antibacterial activity against some gram positive and gram negative bacteria.